THE USE OF SULFUR CONCRETE IN REINFORCED CONCRETE STRUCTURES - I.G‘.Axmedov; I.I.Umarov (Journal of new century innovations, 2023)
Abstract. This scientific article presents the results of experimental studies on the physical and mechanical properties of sulfur concrete and comparative characteristics of strength and deformation characteristics of sulfur concrete with concrete based on Portland cement.